GRAMMATICAL ERRORS MADE BY SECONDARY STUDENTS IN WRITING: FROM INTERLINGUAL TO INTRALINGUAL - Abdur Rofik (JELLT (Journal of English Language and Language Teaching), 2018)
Secondary students need to learn some genres in writing. One of them is recount. This kind of genre involves certain feature perfomance regarding generic structure and language features. However, many students indicated that they had constrains in applying these rules even though the students had gotten special training. This is a case study in writing recount texts held as a competition part of English Olympiade for Secondary Schools in Wonosobo, Indonesia. The purpose is to reveal grammatical errors in students’ writing recount texts. The writer collected the data from students’ written texts compatated in this event. The findings were considered important to improve PS students’ writing perfomance, especially related to grammar problems features and to develop approaches of teaching writing for English teachers toward their students.